Gradient Evolution of Body Colouration in Surface- and Cave-Dwelling Poecilia mexicana and the Role of Phenotype-Assortative Female Mate Choice. (24th September 2013) - Bierbach, David; Penshorn, Marina; Hamfler, Sybille; Herbert, Denise B.; Appel, Jessica; Meyer, Philipp; Slattery, Patrick; Charaf, Sarah; Wolf, Raoul; Völker, Johannes; Berger, Elisabeth A. M.; Dröge, Janis; et al.
Abstract : Ecological speciation assumes reproductive isolation to be the product of ecologically based divergent selection. Beside natural selection, sexual selection via phenotype-assortative mating is thought to promote reproductive isolation. Using the neotropical fish Poecilia mexicana from a system that has been described to undergo incipient ecological speciation in adjacent, but ecologically divergent habitats characterized by the presence or absence of toxic H2 S and darkness in cave habitats, we demonstrate a gradual change in male body colouration along the gradient of light/darkness, including a reduction of ornaments that are under both inter- and intrasexual selection in surface populations. In dichotomous choice tests using video-animated stimuli, we found surface females to prefer males from their own population over the cave phenotype. However, female cave fish, observed on site via infrared techniques, preferred to associate with surface males rather than size-matched cave males, likely reflecting the female preference for better-nourished (in this case: surface) males. Hence, divergent selection on body colouration indeed translates into phenotype-assortative mating in the surface ecotype, by selecting against potential migrant males. Female cave fish, by contrast, do not have a preference for the resident male phenotype, identifying natural selection against migrants imposed by the cave environment as the major driver of the observed reproductive isolation.